Strategies for molecular imaging dementia and neurodegenerative diseases - Bernhard J Schaller (Dove Medical Press, 2008)
Bernhard J SchallerDepartment of Neurosurgery, University of Paris, Paris, FranceAbstract: Dementia represents a heterogeneous term that has evolved to describe the behavioral syndromes associated with a variety of clinical and neuropathological changes during continuing degenerative disease of the brain. As such, there lacks a clear consensus regarding the neuropsychological and other constituent characteristics associated with various cerebrovascular changes in this disease process. But increasing this knowledge has given more insights into memory deterioration in patients suffering from Alzheimer’s disease and other subtypes of dementia. The author reviews current knowledge of the physiological coupling between cerebral blood flow and metabolism in the light of state-of-the-art-imaging methods and its changes in dementia with special reference to Alzheimer’s disease. Different imaging techniques are discussed with respect to their visualizing effect of biochemical, cellular, and/or structural changes in dementia. The pathophysiology of dementia in advanced age is becoming increasingly understood by revealing the underlying basis of neuropsychological changes with current imaging techniques, genetic and pathological features, which suggests that alterations of (neuro)vascular regulatory mechanisms may lead to brain dysfunction and disease. The current view is that cerebrovascular deregulation is seen as a contributor to cerebrovascular pathologies, such as stroke, but also to neurodegenerative conditions, such as Alzheimer’s disease. The better understanding of these (patho)physiological mechanisms may open an approach to new interventional strategies in dementia to enhance neurovascular repair and to protect neurovascular coupling.Keywords: imaging, cognitive impairment, Alzheimer’s disease, cerebrovascular disease, neurovascular coupling